Measurement of Glomerular Filtration Rate by Impulse Synthesis: Clinical Validation and Optimization - Palagi, B.; Villa, F.; Verga, P.; Broggi, Angela; Guzzini, F.; Cozzi, C.; Tomasi, Alessandra; Picozzi, R. (Nuklearmedizin - NuclearMedicine, 1988)
Impulse synthesis is a technique which relies upon the logic of continuous infusion but extracts the clearance value from single-injection data by shifting and adding them until an asymptotic value is attained. This study has been aimed at validating and optimizing clinically the measurement of glomerular filtration rate by impulse synthesis. A single intravenous injection of 51Cr-EDTA has been made in 32 patients and plasma activity monitored over the next 6 h. Glomerular filtration rate computed by a single-exponential fit method (GFR- SEF) has been shown to be significantly (p <0.001) overestimated when compared with the glomerular filtration rate obtained by the impulse synthesis technique (GFR-IS) in spite of an excellent (r = 0.989) linear correlation between the two sets of data. On the other hand, the comparison between GFR-IS and 24-h creatinine clearance has not shown any significant difference. Moreover, we have found that in patients with severe renal failure GFR-IS is overestimated when the sampling time span is shortened to 3 h. On the other hand, GFR-IS is slightly underestimated in patients with severe renal failure when the convolution time interval is increased over a few minutes.